2016 Physics Education Research Conference Proceedings 2016
DOI: 10.1119/perc.2016.pr.086
|View full text |Cite
|
Sign up to set email alerts
|

Student understanding of unit vectors and coordinate systems beyond cartesian coordinates in upper division physics courses

Abstract: In upper division physics courses students are required to work with various coordinate systems. This skill becomes particularly important when learning Electricity and Magnetism, where the most appropriate coordinate system will often depend on the geometry and symmetry of a problem. This study aims to identify and describe "resources" used by students when answering physics questions regarding unit vectors in non-Cartesian coordinate systems, specifically polar coordinates [1]. Data were collected in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 6 publications
1
18
2
Order By: Relevance
“…This pattern matching resulted in the inclusion of unnecessary unit vectors, which frequently appeared as students writing spherical position vectors in the incorrect (but Cartesian-imitating) form ⃗ r ¼ rr þ θθ þ ϕφ. Our initial work on students' thinking on unit vectors in non-Cartesian coordinate systems categorized student thinking into "clusters" of similar but not identical ways that students thought about unit vectors [13]. Specifically, we found that students conflated unit vectors at a point with position vectors to a point.…”
Section: A Background and Purposementioning
confidence: 85%
See 3 more Smart Citations
“…This pattern matching resulted in the inclusion of unnecessary unit vectors, which frequently appeared as students writing spherical position vectors in the incorrect (but Cartesian-imitating) form ⃗ r ¼ rr þ θθ þ ϕφ. Our initial work on students' thinking on unit vectors in non-Cartesian coordinate systems categorized student thinking into "clusters" of similar but not identical ways that students thought about unit vectors [13]. Specifically, we found that students conflated unit vectors at a point with position vectors to a point.…”
Section: A Background and Purposementioning
confidence: 85%
“…Additionally, there was a tendency for students to conflate ideas about the direction of a unit vector having to do with either the location of an object at a point or with the direction of motion of an object at a point. Vega et al [13] further describe a "Unit Vector Cluster" that has essential resources to fit a canonical definition of a unit vector: a unit vector is a vector; has a length of one unit; points in the direction of increasing coordinate; and is dimensionless. The naming of these resources is done for completeness and from an expert perspective, and not all of these resources were identified by the students in the interview sample.…”
Section: A Background and Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Sayre and Wittmann used a resource framework and described 'plasticity' of resources in the process of choice of coordinate system. [8] Vega described student resources in unit vectors in Math Methods [9].…”
Section: A Background and Relevant Prior Workmentioning
confidence: 99%